2016
DOI: 10.1371/journal.pone.0168899
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Transcriptomic Effects of Prebiotics and Synbiotics Delivered In Ovo in Broiler Chickens

Abstract: In ovo delivery of prebiotics and synbiotics in chickens allows for the development of intestinal microflora prior to hatching, which boosts their robustness. The goal of this study was to determine the transcriptomic profile of the spleen (S), cecal tonsils (CT), and large intestine (LI) of adult chickens injected with prebiotics and synbiotics in ovo. On day 12 of embryo development, incubating eggs were injected with prebiotics: inulin alone (P1) or in combination with Lactococcus lactis subsp. lactis IBB29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 59 publications
1
73
0
Order By: Relevance
“…On the other hand, it was suggested that spore forming bacteria such as Clostridium tertium were capable of surviving the disinfection process and penetrating eggs, resulting in contamination ( 118 ). To avoid extensive pathogen infection, prebiotics were delivered in ovo , which is likely fermented by the indigenous embryonic microbiota, inhibiting pathogen proliferation and regulating gene expression of immune responses ( 119 ). Villaluenga et al ( 120 ) reported that injection of raffinose at day 12 of embryonic incubation had the highest amounts of Bifidobacteria in the ceca of 2 day-old broilers.…”
Section: Other Prebioticsmentioning
confidence: 99%
“…On the other hand, it was suggested that spore forming bacteria such as Clostridium tertium were capable of surviving the disinfection process and penetrating eggs, resulting in contamination ( 118 ). To avoid extensive pathogen infection, prebiotics were delivered in ovo , which is likely fermented by the indigenous embryonic microbiota, inhibiting pathogen proliferation and regulating gene expression of immune responses ( 119 ). Villaluenga et al ( 120 ) reported that injection of raffinose at day 12 of embryonic incubation had the highest amounts of Bifidobacteria in the ceca of 2 day-old broilers.…”
Section: Other Prebioticsmentioning
confidence: 99%
“…On a performance level, HS causes losses in feed intake and growth rate. In broiler chickens, chronic HS has been found to significantly reduce (p < 0.01) final body weight (BW) (2.52 kg in TN vs. 3.11 kg in HS) [32,39,40]. In the current study, chronic HS also reduced final BW (p < 0.001), but the difference between TN and HS was almost two times lower than in broiler chickens (2.21 kg in TN vs. 1.94 kg in HS), even with the longer rearing period (42 days in broilers vs. 50 days in slow-growing chickens).…”
Section: Stress-related Gene Expression Signaturesmentioning
confidence: 99%
“…Galactooligosaccharides are potent prebiotics that exert beneficial effects on intestinal microbiota in chickens. Particularly interesting is the possibility of using in ovo technology for the early stimulation of the microbial communities with GOS [32,39,40]. The molecular data on broiler chickens have indicated that HS triggers systemic immune and stress responses, which are balanced by GOS that are delivered in ovo [41].…”
Section: Introductionmentioning
confidence: 99%
“…The gastrointestinal microbiota affects the host organism by regulating immune response, metabolism, digestion, and nutrient absorption [6]. A technology for reprogramming the composition of chicken microbiota at an early stage of embryonic development was developed by administering prebiotics or synbiotics using in ovo technology on day 12 of egg incubation [7,8]. The in ovo administered bioactive substances such as prebiotics like galacto-oligosaccharides (GOS) and inulin and synbiotics like Lactococcus lactis subsp.…”
Section: Introductionmentioning
confidence: 99%